Identifikasi Keragaman Gen Leptin Sebagai Kandidat Gen Kualitas Daging Pada Sapi Pasundan Betina - Nurkamilah, Ghina; Hilmia, Nena; Putranto, Wendry Setiyadi (Jurnal Teknologi Hasil Peternakan, 2025)
Meat quality is influenced by genetic factors,environmental conditions, and their interactions. Variations in thenucleotide sequence of the leptin gene may affect the quality andquantity of leptin hormone, thereby influencing meat quality. Thisstudy aimed to identify the genetic diversity of the leptin genebased on nucleotide sequence mutations in Pasundan cattle raisedat the Ciparanje Beef Cattle Teaching Farm, Faculty of AnimalScience, Universitas Padjadjaran. This Study used 16 DNA samplesfrom female Pasundan cattle were isolated from blood andanalyzed. PCR amplification was performed to amplify a 620 bpfragment of the leptin gene using specific primers designed via theNCBI Primer-BLAST program, with an annealing temperature of59°C. PCR products were evaluated through electrophoresis, andsequencing was carried out to determine the nucleotide sequence.Sequence analysis and genotyping were conducted using BIOEDITand MEGA 11 software. The results revealed a Single NucleotidePolymorphism (SNP) at position g.1047C>T/R25C in the leptingene, with the CT genotype (56.35%) being more frequent than CC(18.8%) and TT (25%). Additionally, several point mutations inintron 1 were identified, including g.806G>A, g.845C>T,g.856G>A, g.868G>C, g.885C>T, g.911C>T, and g.913A>G,consisting of both transition and transversion mutations. Thesefindings indicate that the leptin gene in Pasundan cattle ispolymorphic. Leptin gene polymorphisms in Pasundan cattle arepotentially associated with meat quality traitrs and fat depositionvariation, thus providing a genetic basics for selection to improvethe quality of local cattle